Ragam Estetika Batik Riau terhadap Nilai dan Tradisi Budaya Melayu - Desy Ratna Syahputri (Jurnal Pendidikan dan Penciptaan Seni, 2021)
Batik has been identified as the identity of the Javanese people. Not many people know about Riau-Malay batik, which had a dim existence with the loss of the Daek Lingga and Siak Kingdoms in 1824-1911 AD. Malay batik and Malay traditions have a very strong relationship, where all aspects of culture and art adopt values. the culture contained in the society. The Malay race is a group of people who embraces Islam, this affects all aspects of life to the work of art. The purpose of this paper is to analyze the various aesthetics both in terms of motifs and patterns of present-day Riau Malay batik with the values adopted in society. This research uses descriptive qualitative research methods with data collection techniques through observation, interviews, documentation and library research. The result of this research is the regeneration of the aesthetic variety of present-day Riau Malay batik motifs which adopt 2 types of patterns, namely the veil pattern and the sow pattern. The veil pattern is a vertical, elongated and transcendental meaning. Meanwhile, the sowing pattern is not clear in its philosophy, with the visualization of stacked and dense motifs.